Intrapelvic Migration of the Lag Screw in Intramedullary Nailing - Takasago, Tomoya (Case Rep Orthop, 2014)
Internal fixation with intramedullary devices has gained popularity for the treatment of intertrochanteric femoral fractures, which are common injuries in the elderly. The most common complications are lag screw cut out from the femoral head and femoral fracture at the distal tip of the nail. We report here a rare complication of postoperative lag screw migration into the pelvis with no trauma. The patient was subsequently treated with lag screw removal and revision surgery with total hip arthroplasty. This case demonstrated that optimal fracture reduction and positioning of the lag screw are the most important surgical steps for decreasing the risk of medial migration of the lag screw. Furthermore, to prevent complications, careful attention should be paid to subsequent steps such as precise insertion of the set screw.